2022
DOI: 10.3389/fmicb.2022.1020029
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan co-infections and parasite influence on the efficacy of vaccines against bacterial and viral pathogens

Abstract: A wide range of protozoan pathogens either transmitted by vectors (Plasmodium, Babesia, Leishmania and Trypanosoma), by contaminated food or water (Entamoeba and Giardia), or by sexual contact (Trichomonas) invade various organs in the body and cause prominent human diseases, such as malaria, babesiosis, leishmaniasis, trypanosomiasis, diarrhea, and trichomoniasis. Humans are frequently exposed to multiple pathogens simultaneously, or sequentially in the high-incidence regions to result in co-infections. Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 201 publications
0
12
0
Order By: Relevance
“…Infectious agent research is crucial for understanding the spread of diseases through microorganisms like bacteria, viruses, fungi, protozoa, and parasites. 17 Recognizing and categorizing these agents help identify health hazards and develop effective prevention strategies. Tracing transmission variables and paths can help diagnose diseases, reducing the risk of major consequences or death.…”
Section: Infectious Agentsmentioning
confidence: 99%
“…Infectious agent research is crucial for understanding the spread of diseases through microorganisms like bacteria, viruses, fungi, protozoa, and parasites. 17 Recognizing and categorizing these agents help identify health hazards and develop effective prevention strategies. Tracing transmission variables and paths can help diagnose diseases, reducing the risk of major consequences or death.…”
Section: Infectious Agentsmentioning
confidence: 99%
“…These pathogenic strains have evolved complex mechanisms for invasion and survival in the host. Protozoa frequently go through several sequential stages, that provide them the flexibility to take advantage of various tissues or hosts as they make their way through the challenging transition from existence to transmission, and the sickness often results in tissue damage and subsequent illness ( Zheng et al, 2020 ; Akoolo et al, 2022 ). An assortment of symptoms, from fever and anaemia to cognitive dysfunction and organ failure, can result from the chronic infectious disorders caused by infectious protozoan species that impact the blood, gastrointestinal system, liver, and brain ( Seed, 1996 ).…”
Section: Protozoamentioning
confidence: 99%
“…However, exceptions do occur; for example, Plasmodium spp. infection prior to SARS-CoV-2 infection was reported to contribute to the disease’s poor prognosis and was seen to reduce the incidence of malaria in endemic regions [ 33 , 34 , 35 ]. Furthermore, additional investigations suggested that high exposure to malaria compared to low exposure prior to SARS-CoV-2 infection offered better protection against severe or critical COVID-19 [ 36 ].…”
Section: Bats Pangolins Parasites and Diarylamidines: Making The Conn...mentioning
confidence: 99%
“…Moreover, the authors proposed that vaccine memory was partially destroyed or the accessibility to those memories was prohibited by infection, further highlighting the need for malaria vaccine trials in areas where trypanosomiasis is prevalent. The influence of protozoan infection on bacterial and viral vaccination efficacy and the adaptive immune response is summarized in Figure 4 [ 34 ].…”
Section: Diarylamidines Serine Proteasesmentioning
confidence: 99%
See 1 more Smart Citation